Ag-Decorated Fe3O4@SiO2 Nanorods: Synthesis, Characterization, and Applications in Degradation of Organic Dyes. (30th May 2016) - Li, Chao; Sun, Junjie; Chen, Duo; Han, Guangbing; Yu, Shuyun; Kang, Shishou; Mei, Liangmo
Abstract : Well-dispersed Ag nanoparticles (NPs) are successfully decorated on Fe3 O4 @SiO2 nanorods (NRs) via a facile step-by-step strategy. This method involves coating α -Fe2 O3 NRs with uniform silica layer, reduction in 10% H2 /Ar atmosphere at 450°C to obtain Fe3 O4 @SiO2 NRs, and then depositing Ag NPs on the surface of Fe3 O4 @SiO2 NRs through a sonochemical step. It was found that the as-prepared Ag-decorated magnetic Fe3 O4 @SiO2 NRs (Ag-MNRs) exhibited a higher catalytic efficiency than bare Ag NPs in the degradation of organic dye and could be easily recovered by convenient magnetic separation, which show great application potential for environmental protection applications.